Insuring Good Health: Outcomes and Acceptability of a Participatory Health Insurance Literacy Intervention in Diverse Urban Communities. (June 2019) - Patel, Minal R.; Israel, Barbara A.; Song, Peter X. K.; Hao, Wei; TerHaar, Lindsay; Tariq, Madiha; Lichtenstein, Richard
Background . The U.S. uninsured rate has dropped significantly since the passage of the Affordable Care Act (ACA), yet insurance coverage remains lower in historically marginalized communities than in the overall population. New consumer engagement approaches that involve these populations are needed. The purpose of this study was to evaluate the effectiveness of the Insuring Good Health Intervention, a website and video series designed to improve engagement with health insurance and ACA reforms. The study was designed and implemented using a community-based participatory research approach. Method . We conducted a lagged-control cluster randomized controlled trial to evaluate Insuring Good Health with racially and ethnically diverse adults seeking services in medically underserved areas within the Detroit, Michigan metropolitan area. Outcomes were assessed at baseline and at 6 and 9 months postintervention, and including self-efficacy, knowledge, beliefs, and intention to seek help with insurance navigation and care. Results . Among 243 participants, mean age was 43.4 ( SD = 13) years, and all participants met federal guidelines for poverty. The study had an 86% response rate at 9-month follow-up ( n = 209). Compared with the lagged-control group, intervention participants had more positive beliefs concerning preventive care (estimate 0.51, standard error 0.16; p < .01), and intention to seek help with insurance navigation and care (estimate 0.43, standard error 0.17; p < .001) at 9-month follow-up. Hispanic participants benefitted the most from the intervention, including improved knowledge of health insurance eligibility over 9 months compared with other racial/ethnic groups (estimate −0.97, standard error 0.40, p < .01). Discussion . Insuring Good Health was associated with increased intention to seek help with insurance navigation and care, and improved beliefs around preventive care. Conclusions . Insuring Good Health has the potential to be an important consumer engagement tool to reduce disparities in health insurance coverage and care seeking.